2005
DOI: 10.1029/2005eo050001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between probabilistic seismic hazard analysis and flood frequency analysis

Abstract: Probabilistic seismic hazard analysis (PSHA) was originally developed from the analogous flood or wind problem and was used for risk analysis in a similar way PSHA was extended later to directly incorporate the uncertainty of ground motion. Such direct incorporation of uncertainty has no clear physical basis and makes it difficult to understand, explain, and use PSHA. These difficulties may result in overly conservative seismic design for safeguarding structures such as buildings, bridges, and nuclear power pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…The hazard curves with 16% and 84% confidence levels are equivalent to the hazard curves with median plus/minus one standard deviation. The result from SHA (hazard curve) is similar to results derived by flood-frequency analysis (GUPTA, 1989;WANG and ORMSBEE, 2005) and wind-frequency analysis (SACHS, 1978). As shown in Fig.…”
Section: Alternative Approachsupporting
confidence: 71%
“…The hazard curves with 16% and 84% confidence levels are equivalent to the hazard curves with median plus/minus one standard deviation. The result from SHA (hazard curve) is similar to results derived by flood-frequency analysis (GUPTA, 1989;WANG and ORMSBEE, 2005) and wind-frequency analysis (SACHS, 1978). As shown in Fig.…”
Section: Alternative Approachsupporting
confidence: 71%
“…Risk discussed by Wang and Ormsbee [2005] may differ from that of Holzer. Although there are some different definitions of risk among different professions, it is quantified by three terms: probability, hazard (loss or others), and exposure.…”
Section: Page 303mentioning
confidence: 81%
“…Despite providing an exceptionally clear example of the basics of probabilistic seismic hazard analysis (PSHA), Wang and Ormsbee [2005] nevertheless conclude that ". .…”
Section: Page 303mentioning
confidence: 99%
“…This method was applied to map the probabilistic seismic hazard (including site-effect) in Memphis, Tennessee (Cramer et al 2004(Cramer et al , 2006. Recent studies (Anderson and Brune 1999;Wang et al 2003Wang 2005Wang , 2006Wang , 2007Wang and Ormsbee 2005;Wang and Zhou 2007) showed that equation (3), the heart of PSHA, is invalid because it is based on earthquake science from the 1970s (point source), not on modern earthquake science. As shown in equation (3), f R (r) is introduced to account for the probability that earthquake (a single point) could occur at any point on a fault.…”
Section: Site-specific Probabilistic Seismic Hazard Analysismentioning
confidence: 99%